Going green real-world solutions for the environment - ABC News; Films For The Humanities & Sciences (Firm) (Princeton, N.J. : Films for the Humanities & Sciences, 2007)
Compilation of 12 ABC News stories shows how governments, business and individuals around the world are taking ecofriendly action
Originally broadcast as segments of ABC News
DVD format
Keywords: Green movement; Environmental protection -- Citizen participation; Social responsibility of business; Environmentalism; Documentary television programs